PENGARUH INVESTASI DAN TINGKAT SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI DAN KEMISKINAN DI INDONESIA - Tri Meliniati; Nurjannah Nurjannah; Rinaldi Syahputra (Fakultas Ekonomi Universitas Samudra, 2023)
Abstrak This study aims to analyze the effect of investment and interest rates on economic growth and poverty in Indonesia. The data used in this study is time series data for the 2006-2021 period from the relevant agencies, namely the Indonesian Central Statistics Agency. Methods Data analysis in this study uses path analysis, with the Eviews program. The results of the study with a significance level of 5% indicate that the direct investment variable has a positive and significant effect on economic growth. The interest rate variable directly has a negative and insignificant effect on economic growth in Indonesia. The direct investment variable has a negative and insignificant effect on poverty. The interest rate variable directly has a negative and insignificant effect on poverty, the variable economic growth directly has a negative and significant effect on poverty in Indonesia. While the investment variable indirectly has a negative and insignificant effect on poverty through economic growth in Indonesia, while the interest rate variable has an indirect positive and insignificant effect on poverty through economic growth in Indonesia.